1993
DOI: 10.1152/jappl.1993.74.5.2146
|View full text |Cite
|
Sign up to set email alerts
|

Fructose utilization during exercise in men: rapid conversion of ingested fructose to circulating glucose

Abstract: The aim of the present study was to compare the metabolic fate of repeated doses of fructose or glucose ingested every 30 min during long-duration moderate-intensity exercise in men. Healthy volunteers exercised for 3 h on a treadmill at 45% of their maximal oxygen consumption rate. "Naturally labeled" [13C]glucose or [13C]fructose was given orally at 25-g doses every 30 min (total feeding: 150 g; n = 6 in each group). Substrate utilization was evaluated by indirect calorimetry, and exogenous sugar oxidation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 0 publications
3
29
0
2
Order By: Relevance
“…In the first published dual tracer study in this area, Jentjens et al (22) reported a similar average fructose oxidation efficiency of 63%. Likewise, others have reported 64 -85% lower exogenous-fructose oxidation during prolonged exercise relative to isocaloric quantities of exogenous glucose (1,17,(27)(28)(29), although recently Burelle et al (6) reported only ϳ4% less exogenous fructose oxidized vs. glucose. Lower efficiency for fructose relative to glucose could be due to slower intestinal uptake relating to transporter affinity (42), partial entrapment, storage or metabolism of fructose in the liver, or to preferential uptake and oxidation in contracting tissues (2,6,16).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the first published dual tracer study in this area, Jentjens et al (22) reported a similar average fructose oxidation efficiency of 63%. Likewise, others have reported 64 -85% lower exogenous-fructose oxidation during prolonged exercise relative to isocaloric quantities of exogenous glucose (1,17,(27)(28)(29), although recently Burelle et al (6) reported only ϳ4% less exogenous fructose oxidized vs. glucose. Lower efficiency for fructose relative to glucose could be due to slower intestinal uptake relating to transporter affinity (42), partial entrapment, storage or metabolism of fructose in the liver, or to preferential uptake and oxidation in contracting tissues (2,6,16).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, 28% of the infusion rate suggests a muscle fructose-oxidation rate of 0.42 g/min, similar to the maximal fructose-oxidation rate in present study. In another study, 55-60% of exogenous 13 C-fructose ingested during 3-h of running at 45% V O 2 max was seemingly taken up by the liver and converted to 13 C-glucose that was released into the plasma during the last 90 -180 min of exercise and likely subsequently oxidized by the muscle (17). From these studies, it appears that ingested fructose is less immediately available to the skeletal muscle than glucose, but the liver acts as a reservoir for releasing fructose-derived metabolites that are utilized by the muscle later as a carbon source for oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first, pre-exercise administration of fructose does not induce hyperinsulinemia which is found in pre-exercise administration of glucose and results in a transient hypoglycemia during exercise 41,42) . Furthermore fructose ingestion before exercise enhances fat utilization 43,44) and conserves muscle glycogen 45) during pro-longed exercise. However, several disadvantages also were reported about fructose ingestion; the slower oxidation rate 43,44) and greater gastrointestinal distress than glucose 46) .…”
Section: Energy Supplementationmentioning
confidence: 99%
“…Furthermore fructose ingestion before exercise enhances fat utilization 43,44) and conserves muscle glycogen 45) during pro-longed exercise. However, several disadvantages also were reported about fructose ingestion; the slower oxidation rate 43,44) and greater gastrointestinal distress than glucose 46) . The effects of fructose supplementation on endurance performance are inconsistent.…”
Section: Energy Supplementationmentioning
confidence: 99%